Making publics in a pandemic: Posthuman relationalities, 'viral' intimacies and COVID-19. Issue 3 (2nd September 2021) - Pienaar, Kiran; Flore, Jacinthe; Power, Jennifer; Murphy, Dean
ABSTRACT: The COVID-19 pandemic has placed sexual relationships into sharp focus as strict containment measures, including physical distancing and 'stay at home' restrictions, were initiated to control the spread of the virus. Governments in some jurisdictions prevented contact between non-cohabiting sexual partners (except for couples in pre-existing relationships), while community organisations recommended people avoid casual sexual encounters. This article analyses Australian media articles, commentary and public health messages published during March to October 2020 to explore the normative assumptions underpinning these measures. Applying posthumanist perspectives and Warner's (2002) conceptualisation of 'publics', we consider how COVID-19 public health advice enacts the (human) subject of public health as monogamous, coupled, and living with their partner or nuclear family. Those in non-normative relationships and households are not only excluded from this narrow enactment of the 'ideal' public health subject, but are rendered potentially risky disease vectors by virtue of their alternative kinship arrangements. We explore the implications of these findings for the more-than-human relationalities that shape health inequalities and processes of marginalisation during public health crises, and we offer suggestions for public health measures that address the needs of diverse 'publics'.